Management of Gliomas: Overview of the Latest Technological Advancements and Related Behavioral Drawbacks. (9th August 2015) - Ganau, L.; Paris, M.; Ligarotti, G. K.; Ganau, M.
Abstract : The advancements in basic sciences and the availability of sophisticated technological aids to surgical removal of gliomas have led over the last few years to the rise of innovative surgical strategies, the identification of better prognostic/predictive biomolecular factors, and the development of novel drugs and all are meant to profoundly impact the outcome of patients diagnosed with these aggressive tumours. Unfortunately, the treatment protocols available nowadays still confer only a small survival advantage at a potentially high cost in terms of overall well-being. In this review we identified the potential and limits of the most promising research trends in the management of glioma patients, also highlighting the related externalities. Finally, we focused our attention on the imbalance between the technical and behavioral aspects pertinent to this research area, which ultimately represent the two sides of the same coin.